The postgraduate research handbook: Succeed with your MA, MPhil, EdD and PhD - Wisker, Gina (New York Palgrave Macmillan, 2008)
The second edition of this best-selling book is aslively and accessible as the first edition. Advice, support and both active and reflective tasks take the students through the stages of research as well as encouraging them to consider social and cultural issues, such as working with their supervisor and other researchers.